Pendampingan Masyarakat dalam Optimalisasi Administrasi Desa melalui Pelatihan Tata Kelola Dokumen - Putra, Arie Setya; Yuniarthe, Yodhi; Fawa’ati, Teuku Muhamad; Brajanoto, Destoprani; Dirayati, Fadhilah; Hartanto, M Budi; Marlina, Iin (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Well-organized village administration is an essential factor in supporting transparency and government effectiveness. However, many villages still face challenges in systematically managing administrative documents. This community service activity aims to provide training to village officials on effective document management. The method used in this activity is practice-based training with a participatory approach. The results of this training show an increase in understanding and skills in village document management. With this assistance, it is expected that village administration will be more structured and accountable.